2012
DOI: 10.1021/bi300260s
|View full text |Cite
|
Sign up to set email alerts
|

The Linker of the Interferon Response Factor 3 Transcription Factor Is Not Unfolded

Abstract: Interferon response factor 3 (IRF-3) is a transcription factor that plays an essential role in controlling the synthesis of interferon-β (IFN-β) and is a protein consisting of two well-defined domains, the N-terminal DNA-binding and the C-terminal dimerization domains, connected by a 75-residue linker, supposedly unfolded. However, it was not clear whether in intact IRF-3 this linker segment of the chain, which carries the nuclear export signal and includes a region of high helical propensity, remains unfolded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…It shows that the linker region most likely adopts a folded conformation, where it may interact with the DBD and IAD domains located at either end of the molecule. This finding is supported by our CD studies and a report suggesting that the linker in IRF3 is not unfolded but may also adopt a folded conformation (58). Thus, our SAXS IRF4 envelope may represent the general domain architecture for all IRF proteins and suggest that the linker domain may play a role in the regulation of IRF function.…”
Section: Discussionsupporting
confidence: 88%
“…It shows that the linker region most likely adopts a folded conformation, where it may interact with the DBD and IAD domains located at either end of the molecule. This finding is supported by our CD studies and a report suggesting that the linker in IRF3 is not unfolded but may also adopt a folded conformation (58). Thus, our SAXS IRF4 envelope may represent the general domain architecture for all IRF proteins and suggest that the linker domain may play a role in the regulation of IRF function.…”
Section: Discussionsupporting
confidence: 88%
“…Recent structural analysis indicated that the linker represents a folded structural domain. 28,29 Strong binding of the dimeric IRF3 to the PRDII–PRDI tandem recognition sites needs to bend DNA by about 100 o (Figure 5). Our current study shows that the phosphorylation status at Ser123, Ser173 and Thr180 residues of IRF3(5D) affects its transactivation activity.…”
Section: Discussionmentioning
confidence: 99%
“…The domain structure and activation mechanism of IRF3 are very similar to those of Smads. The structural analysis indicated dimeric IRF3 bound to the PRDII–PRDI tandem recognition sites cause a bending of DNA, 28,29 so it is possible that the phosphorylation of IRF3 linker region may reduce the flexibility required for the strong binding to the target DNA (Figure 5). Consequently, it may then affect the proper assembly of the transactivation complexes.…”
Section: Discussionmentioning
confidence: 99%
“…However, the full-length IRF3 structure is unavailable, and it is therefore not known how the DBD and the IAD are arranged in the IRF3 monomer and dimer (11,44,45). The linker region is shown to be partially helical in the full-length IRF3 protein, while it is not structured when either of the domains is absent (46). Thus, the intact linker region may also be involved in N pro binding.…”
Section: Discussionmentioning
confidence: 99%